Microplastic tracking from Pacific garbage to Northern Indonesia Sea - Agung Ramos; Noir P Purba; Ibnu Faizal; Yeni Mulyani; Mega L. Syamsuddin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study aims to examine the pattern of microplastic waste movement of Pacific Garbage Patch (PGP) that has the potential to enter the north of Indonesia sea. This study very important because microplastic affected the regional tourism activities, water pollution, and economics of fisherman and local society. The impact is very widerange to local and national economics. The method used is a simulation and descriptive analysis. The simulation method used is hydrodynamic simulation and trajectory of particles conducted for 365 days in 2016. The study areas in this study include eastern Indonesia, the Philippines, and the Pacific Ocean. The data used are wind, tidal, bathymetry, microplastic weight, and microplastic flux. The simulation results show the movement of microplastic at point source 1 tends to the northeast with a clockwise circular motion. The simulation results at source point 2 indicate that the microplastic movement tends to revolve around the source point in a clockwise circular motion. The result of simulation of source point 3 shows that the microplastic movement tends to the north with the circular motion and left-right movement. The displacement of microplastic particles within a year is only 0.11 - 8.94 km from the source point. This study showed that within a year, microplastic waste from PGP does not have the potential to enter the waters of Indonesia.